Repositioning of spa premises into the context of Islamic built environment and Muslim friendly attributes - Othman, Rashidi; Mohd Noor, Nur Fadhlina; Ahmad, Nurliyana; Aishah, Nurwina; Hashim, Khairusy Syakirin Has-Yun; Mahamod, Lukman Hakim; Ahmad Fadzillah, Nurrulhidayah (2018)
Spas have become increasingly popular and have emerged as important profit centers for hotels. However, the uniqueness of this market has been largely overlooked in terms of Shari’ah compliant to cater for Muslim needs. Therefore, the purpose of this study is to the repositioning of spa typologies, spatial organization and social interaction in the context of Islamic built environment. A survey was administered at four case studies of different spas typologies in Kuala Lumpur and Selangor to identify the new dimensions of Muslim-friendly spa concept. Cluster analysis was then applied to classify spa premises into different groups based on the typologies, services and spatial organization. Based on the finding, the spa that follows the Shari'ah compliance brings remuneration and advance the excellence of spa by implementing space organization of spa, which includes security, privacy, also gender segregation in space including the spa design component. It is crucial that Malaysia takes concrete steps to develop Islamic or Shari’ah compliant tourism internationally. This research is intended to provide further information on the understanding, practice, features, and requirements for Muslim-friendly spa which will help boost Malaysia’s potential to become as one of the prominent destinations for Islamic or Shari’ah compliant tourism.